SCANDAL-a facility for elastic neutron scattering studies in the 50-130 MeV range - J. Blomgren (2018)
© Copyright owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike Licence. A facility for detection of scattered neutrons in the energy interval 50-130 MeV, SCANDAL (SCAttered Nucleon Detection AssembLy), is part of the standard detection system at the 20-180 MeV neutron beam facility of the The Svedberg Laboratory, Uppsala. It has primarily been used for studies of elastic neutron scattering, but it has been employed for (n,p) and (n,d) reaction experiments as well. Results of recent experiments are presented to illustrate the performance of the spectrometer. Recently, the facility has been upgraded to perform also (n,Xn'[) experiments. For this purpose, a new converter, CLODIA, has been developed and installed. Preliminary results of the commissioning of CLODIA will be presented.